Cleaning false information in social networks with herd behaviours : a simulation study - Zhou, Lin (2017)
The rumor spreading in social networks could be considered as “infection of the mind” among people. In human society, each person’s mind may be affected by people around him/her, especially by those with stronger influences. In this dissertation we attempt to analyze the effects of herd behaviors on opinion formation in human society when we tend to clean up the rumor spreading. The SIR model is adopted in simulating the spread and cleaning up of the rumor. To evaluate the effects of herd behaviors, we test on different cases with the classic SIR model and SIR model with herd behavior respectively. By comparing between different cases, we could figure out the factors that obstruct and promote the rumor cleaning process respectively, and the roles that are well-known and influential individuals may play in rumor cleaning process.